Studi Living Qur’an: Pembacaan Ayat-Ayat Al-Qur’an Dalam Prosesi Isi Qubur Di Kota Bangkok Thailand - M. Zaenal Arifin; Diah Handayani; Sarawut Phantawi; Nattapon Nipapan (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2016)
Al-Qur’an becomes a part of life of Muslims in Bangkok Thailand. Reading Al-Qur’an becomes a value to the Muslim community there, especially to send the reward of reciting the Quran to Muslims who had died that they call as ‘isi qubur’ ritual. This research is qualitative research, which is a case study on the implementation of ‘isi qubur’ procession in the city of Bangkok Thailand. The researchers used the method of observation, interviews and documentation to obtain the necessary data. After the stage of data analysis, the researchers concluded as follows; Scriptures used in the procession of ‘isi qubur’ are 13 kinds, namely: surah al-Fatihah (1): verses 1-7, Surah Yasin (36): 1-83 verse, Surah al-Ikhlas (112): verses 1-4, surah al-Falaq (113) verses 1-5, surah al-Nas (114) verses 1-6, surah al-Baqarah (2) verses 1-5, surah al-Baqarah (2) verse 163, surah al-Baqarah (2) verse 225, surah al-Baqarah (2) verse 284-286, surah Hud (11): 73, surah al-Ahzab (33) verse 33, surah al-Ahzab (33) verse 56, surah Ali Imran ( 3) verse 173. The reasons of the use of those Al-Qur’an verses in the procession of ‘isi qubur’ are: firstly in general the majority of scholars do not have different opinion that reading Al-Qur’an is basically justified by religion and a reward, anytime and in any place. Secondly, in particular a lot of information in Al-Qur’an and Hadith that can serve as strong arguments by scholars for the arrival reward of reading Al-Qur’an and prayer for those who have died.